OPTIMASI FORMULA PEMBUATAN SABUN PADAT ANTISEPTIK ALAMI DENGAN PENAMBAHAN EKSTRAK DAUN SIRIH HIJAU (Piper betle L) - Aznury, Martha; Hajar, ibnu; Serlina, Ayu (KINETIKA, 2021)
Green betel leaf (Piper betle L) is a natural antiseptic with phenol (carvacrol) and phenylpropane (eugenol and kavikol) which functions as an antiseptic (very strong bactericide and fungicide). phenol which is a toxic compound resulting in disrupted three-dimensional protein structure causing damage to the bacterial cell wall. So that soap containing natural antiseptic from betel leaf can kill bacteria. The purpose of this study was to determine the benefits of green betel leaf and to obtain the best formulation of natural antiseptic solid soap with the addition of green betel leaf extract. The composition of the oils used in making solid soap is palm oil, coconut oil and olive oil. Tests carried out on solid soap include pH test, water content test, free fatty acid content, free alkaline content, and mineral oil based on SNI 06-3532-1994 as well as testing for many bacteria. Based on the analysis, it is known that the soap formula with the best oil composition variations is the composition of palm oil, coconut oil and olive oil with a ratio of 1: 2: 2 and the addition of green betel leaf extract as a natural antiseptic is 3gr.